Webometric ranking of European universities - Pavlina, Krešimir (Array, 2012)
In year 2004 Aguillo and colleagues launched the Webometrics Ranking of World's Universities (www.webometrics.info), the ranking of universities by their presence on the Internet with the aim of promoting and enriching the content of university web pages. This paper presents research which gathered data for 12.000 universities using Aguillo’s methodology. Data analysis revealed shortcomings in the implementation of the algorithm used by Aguillo et al. for ranking of world universities, which negatively influenced ranking of 768 world universities (6.4% of universities represented in ranking). Shortcomings in implementation will be demonstrated on example of University of Zagreb. It will be presented that by correct application of the algorithm, ranking of affected universities extremely improves, which changes overall ranking of other universities.